Analisa Variasi Saringan Mesin Penggiling Daging Ayam Kapasitas 1 Kg Terhadap Waktu - Ricki Kristanto Napitupulu; Jhon Sufriadi Purba; Winfrontstein Naibaho (Jurnal Teknik Mesin, 2022)
Bakso is a type of chicken meat ball that is commonly found in Indonesian cuisine. Currently, chicken meatballs are one of the processed chicken meat products that have a particular taste. The biggest energy contribution comes from protein, which reaches 60 percent, followed by fat as much as 38% and carbohydrates as much as 2%. The high public demand for processed products such as chicken meatballs has resulted in most shops, from stalls, school canteens, grocery stores, to supermarkets selling chicken meatballs. Before the existence of modern meat grinding machines, the process of grinding chicken meat was very difficult, but now, with advances in technology, there are many grinding machines on the market that simplify the process of grinding meat. The business of making and selling chicken meatballs has attracted the interest of several community business groups with small and medium scale businesses. In order for the business of producing and selling chicken to meet public demand both in terms of quantity and in terms of quality, good planning and management is needed. The design method used includes grinding machine product design. The result of the design that has been done is the output diameter of the meat with a size of 5 mm with the appropriate results (fine on average). Where the diameter of 2 mm and 3 mm produces chicken meat that comes out very slowly and is very smooth and causes the meat to melt and the chicken meat comes out fast and smooth. Thus, it can be concluded that a chicken meat grinder machine can grind 1 kg of chicken meat in 1 minute and the appropriate output hole size is 5 mm with a smooth and fast output of chicken meat.